Dyadic Coping in Couples: A Conceptual Integration and a Review of the Empirical Literature - Falconier, Mariana Karin; Kuhn, Rebekka (Frontiers in Psychology, 2019)
The present review on dyadic coping (DC) aims at providing a critical integration of both the conceptual and empirical DC literature and overcoming the limitations of past reviews by (a) describing, comparing, and integrating all the DC models, (b) presenting and integrating findings from studies based on DC models, and (c) suggesting directions for further research. The DC models identified and compared include: The congruence model (Revenson, 1994), the relationship-focused model (Coyne & Smith, 1991; O’Brien & DeLongis, 1996), the communal coping model (Lyons, Mickelson, Sullivan, & Coyne, 1998), the systemic-transactional model (Bodenmann, 1995, 1997); the relational-cultural model (Kayser, Andrade, Watson, 2007), and the developmental-contextual coping model (Berg & Upchurch, 2007). After discussing each DC model, we advance a conceptual integration of all models, which serves as the framework to organize the review of the empirical literature. This integration includes the following DC dimensions: (a) Stress Communication, (b) Positive DC by One Partner (supportive DC, empathic responding, delegated DC, active engagement), (c) Positive Conjoint DC (common, collaborative, communal, mutual responsiveness); (d) Negative DC by One Partner (protective buffering, overprotection, and hostility/ambivalence), and (e) Negative Conjoint DC (common negative DC, disengaged avoidance). Developmental, relational, and contextual variables are included as factors shaping DC. To be included in the empirical review, articles had to be published in or a peer-reviewed journal in English and/or German before 2017 and include an original empirical study guided by one of the DC models. The review included 139 studies and, with the exception of CM whose findings were discussed separately, findings were presented for overall DC and each of the dimensions identified in the conceptual integration. Findings were grouped also according to whether the stressor related or not to a medical or mental health condition. Demographic and cultural factors affecting DC were discussed. Overall, the empirical review suggests that in Western couples, positive individual and conjoint DC forms, taken together or separately, have individual and relational benefits for couples coping with stress in general and/or mental health or medical stressors. Research on DC can be expanded to include other populations and stressors and use improved designs.